A Novel Ethanol Induced and Stabilized Hierarchical Nanorods: Hydroxyapatite Nanopeanut. Issue 6 (7th April 2015) - Ji, Xiujie; Su, Penghe; Liu, Chao; Song, Jun; Liu, Chaoya; Li, Jia; Tan, Hongliang; Wu, Fangfang; Yang, Liyun; Fu, Ranran; Tang, Chengchun; Cheng, Bowen; et al.
<x xml:space="preserve">Abstract</x> Hydroxyapatite (HA) nanopeanut, hierarchical nanorods covered with nanopits on surface, was successfully synthesized via a novel ethanol induced and stabilized route. Ca(NO3)2, H3PO4, and NaOH were used as calcium source, phosphorus source, and pH adjusting agent, respectively. X‐ray diffraction analysis showed that hierarchical nanorods are well crystallized and present a pure hexagonal Ca10(PO4)6(OH)2. Transmission electron microscopy (TEM) exhibited that the nanorods are of 50–210 nm in length and 22–52 nm in width. The nanopits of 3–12 nm in diameter in the surface were also confirmed and calculated by nitrogen adsorption/desorption isotherms, which is well consistent with TEM observation. Ethanol as the sole functional organic molecule played the roles of improving the HA crystallization, inducing the nucleation and growth of HA nanorods, as well as inducing and stablizing the nanopits in surface. The ethanol‐assisted synthesis mechanism of HA nanopeanut was proposed and discussed in thermodynamics. This novel ethanol‐assisted route is green, facile, efficient, low‐cost, and surfactant‐free and may be useful for the synthesis of other hierarchical materials.